A system for monitoring mutation-in-progress : a study of adaptive mutation to Ciprofloxacin resistance in Staphylococcus aureus - Sutandar, Andiyanto (2008)
In nature, evolution progresses to assure the survival of the strongest of a species. With each mutation, those characteristics that best assure the survival of the species are propagated through successive, on-going mutations. As there is no known method to monitor such mutation-in-progress, the objective of this research was to devise a technique to monitor the progression of mutation. Pathogens are known to survive (mutate to gain resistance) in an antibiotic-containing environment. One such pathogen, staphylococcus aureus is known to cause diseases ranging from superficial dermatological lesions to systemic and life threatening infections such as endocarditis. One particular strain of staphylococcus aureus - methicillin resistant Staphylococcus aureus (MRSA) - is known to be resistant to almost all antibiotics. A pilot study established that it is feasible to monitor the growth of staphylococcus aureus using overnight cultures as well as direct culture of nasal swab through visible spectroscopy. Using such spectroscopic technique, it was possible to discriminate between methicillin susceptible and resistant strains of Staphylococcus aureus. Based on these results, a novel system coined the System for Monitoring Mutation-in-Progress (SMMIP) was devised. SMMIP allows nutrients to be replenished and extracted to allow for long term tracking. In this study, the use of SMMIP to monitor the mutation-in-progress is demonstrated through the adaptation of ciprofloxacin resistance, a fluoroquinolone antibiotic, in Staphylococcus aureus. SMMIP was successful in automatically monitoring the growth of methicillin susceptible Staphylococcus aureus (MSSA) ATCC 29213 in Mannitol Salt Broth (MSB) containing ciprofloxacin. Resistant mutants in MSB containing 0.5 ug/ml of ciprofloxacin emerged on Days 6, 4, and 7 from samples containing initial inocula of 6.0 x 10^6 CFU/ml, 1.3 x 10^7 CFU/ml, and 1.3 x 10^8 CFU/ml respectively. The ciprofloxacin mutants were detected by monitoring wavelength shifts of the acidogenic profiles of the growth medium. The SMMIP measures the growth of mutants on the same day that an increase of viable count was observed. It also requires fewer resources than conventional standard plate count and Population Analysis Profile (PAP) techniques. Sequencing of the quinolone resistant determining region (QRDR) gene sections are then performed to further confirm the existence of mutants. The Scanning Electron Microscope (SEM) images of the bacteria show the exploded state of Staphylococcus aureus. The release of the cell content correlated well to the alkalization and clearing of the growth medium seen by the spectroscopic readings. The scanning microscopy images also confirm the presence of viable bacteria with normal morphological shape. SMMIP can be utilized to study the interaction between various antibiotics and bacteria provided that there is an inducible colour change in the sample. With the built-in method to replenish and extract the nutrient, simulations of more diverse drug profiles can be carried out.